Biotechnological, biomedical, and agronomical applications of plant protease inhibitors with high stability: A systematic review. (March 2020) - Cotabarren, Juliana; Lufrano, Daniela; Parisi, Mónica Graciela; Obregón, Walter David
Graphical abstract: Highlights: Plant PPIs are small molecules with remarkable physical and chemical stability. PPIs have a number of applications in biomedicine, biotechnology, food industry and diagnosis. PPIs belong to the natural compounds with physicochemical stability and biologic activities. Abstract: Protease inhibitors (PIs) are regulatory proteins found in numerous animal tissues and fluids, plants, and microorganisms that reduce and inhibit the exacerbated and uncontrolled activity of the target proteases. Specific PIs are also effective tools for inactivating proteases involved in human diseases like arthritis, pancreatitis, hepatitis, cancer, AIDS, thrombosis, emphysema, hypertension, and muscular dystrophy among others. Plant PIs—small peptides with a high content of cystine residues in disulfide bridges—possess a remarkable resistance to heat treatment and a high stability against shifts in pH, denaturing agents, ionic strength, and proteolysis. In recent years, novel biologic activities have been reported for plant PIs, including antimicrobial, anticoagulant, antioxidant action plus inhibition of tumor-cell growth; thus pointing to possible applications in medicine, agriculture, and biotechnology. In this review, we provide a comparative overview of plant-PIs classifying them in four groups according of their thermal and pH stability (high stability and hyperstable -to temperature and to pHs-, respectively), then emphasizing the relevance of the physicochemical characteristics of these proteins for potential biotechnological and industrial applications. Finally, we analyze the biologic activities of the stable protease inhibitors previously characterized that are the most relevant to potential applications in biomedicine, the food industry, and agriculture.